Upaya Penanggulangan Gelandangan Dan Pengemis Melalui Program Rehabilitasi Sosial Di Dinas Sosial Kota Medan - M.Rafli Muhajir; fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
in writing The purpose of writing this article is to look at the Medan City government's efforts to deal with the need for Social Welfare Services (PPKS), especially Street Children based on Medan Mayor Regulation Number 6 of 2003 concerning the Prohibition of Begging and Begging in Medan City which is carried out by the Medan City Social Service in coordination with the Civil Service Police Unit. Praja (Satpol PP) of Medan City and in collaboration with the Medan City Police. This journal discusses the process of dealing with Homeless and Beggars through the Social Rehabilitation Program carried out by the Medan City Social Service. Social rehabilitation is basically to restore and develop the abilities of someone who experiences social dysfunction so that they can carry out their social functions properly. The method in writing this journal is to use the group work stage method in general (general).